Tourism and economic growth in Malaysia: Evidence from multivariate causality tests - Kadir, Norsiah; Abdullah, Mat Saad (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
The aim of this study is to investigate the presence as well as direction of (significant) causal relationship between the Malaysian international tourism receipts and real growth in its national economy. Based on the sample period of I994 through 2004, the data are examined from the perspective of multivariate causality procedure. Major finding of the study is twofold: First, international tourism receipts and real economic growth are found to be significantly cointegrated. Secondly, multivariate causality test based on the error correction model reveals that the Granger causality between international tourism receipts and real economic growth is unidirectional - running from real economic growth to international tourism receipts. The practical implication that could be conceived from this 'growth-led tourism' finding is that, as the Malaysian economy is growing, accelerated growth of socio-economic activities as well as business opportunities in its tourism-related sectors could be expected.